THE INFLUENCE OF A DIFFERENTIATED APPROACH ON THE FORMATION OF A HEALTHY LIFESTYLE AMONG SCHOOLCHILDREN (Scientific journal of the Fergana State University, 2025)
The purpose of this study is to study the impact of a differentiated approach on the formation of a healthy lifestyle among schoolchildren. The study involved 150 students of secondary schools in the Ferghana region aged 11 to 15 years. The use of differentiated physical training programs made it possible to take into account the individual characteristics of students and improve their physical development. The results showed that the use of a differentiated approach helps to improve physical activity, increase motivation to play sports and form positive health habits.